TENDENCIAS Y PERSPECTIVAS SOBRE PFAS EN AGUA POTABLE Y SU REGULACIÓN (Nativa, 2026)
Trends and perspectives on PFAS in drinking water and its regulation ABSTRACT: PFAS are a concern due to their persistence, toxicity, and presence in drinking water, with widespread exposure and regulations under review, demanding a quantitative synthesis to guide decision-making. The objective was to characterize the scientific and regulatory evolution regarding PFAS in drinking water and to identify stakeholders, networks, milestones, and gaps. A bibliometric analysis was conducted in Scopus up to August 24, 2025, with 3581 documents, processed using Bibliometrix 5.1.1 and VOSviewer 1.6.19, applying Lotka's and Bradford's laws, co-authorship, RPYS, fractional counting, and thematic maps. The results indicate an annual growth rate of 25.14%, a peak of 623 articles in 2024, 11,291 authors and 6.54 co-authors per document, international co-authorship of 27.62%, 278 sources, a top ten authorship accounting for 58% of the articles, leading positions held by the United States and China, and a peak of 16,216 citations in 2020. There are also signs of a shift towards class-based approaches and increased focus on risk, biomonitoring, and treatment. The study concludes that the field is young and already well-established, with regulatory utility, although gaps remain in the standardization of group metrics, in linking plant performance and human exposure, in cost assessment, in waste management, and in risk communication.Keywords: Perfluoroalkyl and polyfluoroalkyl substances; perennial chemical compounds; drinking water; environmental regulation; bibliometrics; risk assessment; bibliometric analysis.